Penerapan model connecting, organizing, reflecting, extending (CORE) untuk meningkatkan pemahaman konsep peninggalan sejarah kerajaan hindu-buddha dan islam pada peserta didik kelas IV - S A Sanjaya; Hadi Mulyono; Hadiyah Hadiyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This research aims to improve understanding of the concept of historical heritage ofthe Hindu-Buddhist and Islamic kingdoms in Indonesia using the CORE model. This researchis a Classroom Action Research conducted in 2 cycles. The research subjects were students inthe 4th grade elementary school Sukoharjo numbering as many as 30 students. Data collectiontechniques used were tests, documentation, interviews, and observations. The data analysis isan interactive analysis model. the average value of understanding the concept before theaction (pre-cycle) was only 34.5%, then 59.5% in cycle 1, and 79.5% in cycle 2. Based on theresults of the study concluded that the CORE model can improve understanding of the conceptof historical heritage of the Hindu-Buddhist and Islamic kingdoms in Indonesia in grade 4students of elementary school Sukoharjo.